Does social network site use buffer against well-being loss when older adults face reduced functional ability?. (May 2017) - van Ingen, Erik; Rains, Stephen A.; Wright, Kevin B.
Abstract: We examine the role of the Internet in dealing with problems in later life by analyzing whether direct and buffering models of social support can be applied to social network site (SNS) use. Whereas the direct model implies a positive effect of time spent using SNSs on subjective well-being, and a negative effect on social loneliness, the buffering model suggests that SNS use should reduce the (negative) consequences of stressors. Using a large, longitudinal survey from the Netherlands, we find evidence for the buffering model but not for the direct-effects model. Functional disability had a negative impact on (changes in) well-being and this effect was smaller when older individuals used SNSs more. Furthermore, we found a similar buffering effect of making online purchases, which we interpret as support for the idea that replacing offline with online activities may be a compensation strategy. This implies that Internet use may play a role in coping with health-related problems connected to later stages of the life course. Highlights: We study whether the Internet plays a role in dealing with age-related problems. SNS use reduced the negative effect of physical disability on well-being. Time spent on making online purchases had a similar effect. SNS use reduced the positive effect of physical disability on social loneliness. SNS use had no direct effects on well-being or social loneliness.